UPAYA PENCEGAHAN KEBOCORAN DATA KONSUMEN MELALUI PENGESAHAN RUU PERLINDUNGAN DATA PRIBADI (STUDI KASUS E-COMMERCE BHINNEKA.COM) - Deanne Destriani Firmansyah Putri (2021)
The progression of the technology which accompanied by development of the internet are growing rapidly. In this era of globalization, we've made it easier by the since emerged of the internet. Like shopping, we can buy our needs by online shopping application through some e-commerces. The consumers of e-commerce in Indonesia has increased until 38,3% after this pandemic happened, this thing actually makes the level of internet security more vulnerable because many registrants just register their data into the e-commerce. So many cases about data leakage, like it happened in e-commerce Bhinneka.com. Therefore, we still facing problems regarding about data leakage and how to prevent data leakage, what our behaviour regarding data leakage perpetrators and what the responsibility by the e-commerce, and then to legalization The Protection of Personal Data Bill is very important, if this bill has legalized it can answer all problems about data leakage. The research method used is normative juridical with statute approach and case approach. In this research will be explained how important to legalization The Protection of Personal Data Bill, because many important articles which can be applied to the consumers who feel disadvantaged by data leakage perpetrators and public will get legal certainty to deal with data leakage problems.